Icelandic primary and lower secondary school teacher knowledge and methods for supporting students with ADHD - Guðmundsdóttir, Bergljót Gyða; Karlsdóttir, Erla; Sigmarsdóttir, Margrét (Netla, 2021)
Effective prevention and intervention for children and youth with neurodevelopmental disorders, including attention-deficit hyperactivity disorder (ADHD), is crucial to supporting their positive development. School staff are often the primary agents of intervention for this group of students and it is important, therefore, that they be afforded opportunities and training in providing effective supports, based on best practices. The aim of the present study was to investigate Icelandic primary and lower secondary school teachers’ sources of knowledge and perceived preparation regarding ADHD, their use of various support/instructional and progress monitoring practices for this group of students, and their perceptions of various aspects of their professional environment, in a sample of N = 592 (88.5% female) in-service elementary school teachers in Iceland, who taught at least one student with ADHD that school year. Participants were recruited via email sent to all members of the Association of Teachers in Primary and Lower Secondary Schools in Iceland and invited to participate in an online survey (13% response rate). The study was approved by the National Bioethics Committee in Iceland (reference no. VSN- 19-070). Consistent with previous findings, results revealed that most participants (91%) reported deriving knowledge about ADHD from their experience of teaching students with the disorder. Teaching experience was significantly associated with participants’ self- -reported level of preparation for supporting students with ADHD. Specifically, participants with greater teaching experience were more likely to report that their pre-service training (e.g., teacher education program) prepared them poorly for teaching students with ADHD, compared to participants with fewer years of teaching experience. This may suggest that in recent years, teacher education program development in Iceland has led to enhanced preparation of future teachers in working with students with ADHD, although more research is needed to better ...